APPLICATION OF PROBLEM BASED LEARNING MODELS ON NATURAL SCIENCES TO IMPROVE MOTIVATION AND LEARNING OUTCOMES - Yusa, Ilham Widia; Rakhmawan, Aditya; Suwandi, Suwandi (Jurnal Pendidikan Matematika dan IPA, 2023)
The purpose of this study is to analyze the motivation and learning outcomes of science after applying the problem based learning (PBL) models. This research is a classroom action research (CAR) which was carried out in 2 cycles, each cycle using the PBL model. The research subjects were 32 students of class VIII E odd semester at SMP Negeri 3 Jombang. The data collection technique used a learning motivation questionnaire which was conducted preconditioning, post-cycle 1 and post-cycle 2, and data on student science learning outcomes obtained from the pretest conducted before PBL was applied and posttest after PBL. The data analysis technique used is descriptive quantitative analysis, analysis of the results of the questionnaire on learning motivation using a Likert scale and analysis of student learning outcomes using the paired sample T test using SPSS 20. The results of this study indicate the average precondition learning motivation is 56.40%, post cycle I 72.81% and post cycle II 83.73%. the increase in precondition-post-cycle I was 16.412% and the increase in post-cycle 1-post-cycle II was 10.918%. The results of the paired sample T test have a significant value of 0.000. This shows that learning using PBL can be effective in increasing students' motivation and learning outcomes in science learning.